2020
DOI: 10.3390/jcm9113727
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Delivery during the COVID-19 Pandemic and Immediate Postpartum Maternal Cognitive Function

Abstract: Survivors of the 2003 SARS epidemic were found to have higher rates of adverse mental conditions. This study aimed to assess cognitive function in women delivering during the COVID-19 pandemic, as compared to women who delivered before the COVID-19 pandemic. A cohort study was performed during the immediate postpartum period of women delivering singletons at term. Cognitive function was assessed using an objective neurocognitive test (Symbol Digit Modalities Test SDMT90, SDMT4) and a subjective self-estimation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Postpartum depression disorder is the most common postpartum illness among women 9 . According to the DSM‐5 definition, PPD occurs 4 weeks after delivery while others define it as commencing at any time in the first year after delivery 10 . Postpartum depression threatens not only the health of mothers but also the health of infants, and infants of depressed mothers may have developmental disorders, reduced cognitive function, as well as problems pertaining to social communication with their parents and peers 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postpartum depression disorder is the most common postpartum illness among women 9 . According to the DSM‐5 definition, PPD occurs 4 weeks after delivery while others define it as commencing at any time in the first year after delivery 10 . Postpartum depression threatens not only the health of mothers but also the health of infants, and infants of depressed mothers may have developmental disorders, reduced cognitive function, as well as problems pertaining to social communication with their parents and peers 11 …”
Section: Introductionmentioning
confidence: 99%
“…9 According to the DSM-5 definition, PPD occurs 4 weeks after delivery while others define it as commencing at any time in the first year after delivery. 10 Postpartum depression threatens not only the health of mothers but also the health of infants, and infants of depressed mothers may have developmental disorders, reduced cognitive function, as well as problems pertaining to social communication with their parents and peers. 11 Approximately 10%-16% of women in the postpartum period experience a period of major depression and many of them also suffer from anxiety disorders.…”
mentioning
confidence: 99%
“…This left 45 papers for full-text screening, of which 16 were excluded: data for postpartum women were not reported separately in nine studies ( Li et al, 2021 ; Masters et al, 2021 ; Perzow et al, 2021 ; Wang et al, 2021 ; Liu et al, 2021 ; Stepowicz et al, 2020 ; Xue et al, 2021 ; Chaves et al, 2022 ; Farewell et al, 2020 ); psychological health symptoms were not screened by validated scales in three studies ( Dib et al, 2020 ; Ollivier et al, 2021 ; Jafree et al, 2021 ), and four studies reported the mean score for psychological health symptoms instead of prevalence ( Mayopoulos et al, 2021 ; McFarland et al, 2021 ; Shayganfard et al, 2020 ; Fernandes et al, 2021 ). Finally, 29 articles were included in the meta-analysis ( Loret de Mola et al, 2021 ; Pariente et al, 2020 ; Racine et al, 2021 ; Silverman et al, 2020 ; An et al, 2021 ; Basu et al, 2021 ; Bo et al, 2020 ; Boekhorst et al, 2021 ; Ceulemans et al, 2021 ; Ceulemans et al, 2020 ; Chrzan-Dętkoś et al, 2021 ; Fallon et al, 2021 ; Guvenc et al, 2021 ; Hamami et al, 2020 ; Hiiragi et al, 2021 ; Hui et al, 2021 ; Liang et al, 2020 ; Lorentz et al, 2020 ; Mariño-Narvaez et al, 2021 ; Molgora and Accordini, 2020 ; Oskovi-Kaplan et al, 2021 ; Ostacoli et al, 2020 ; Spinola et al, 2020 ; Stojanov et al, 2021 ; Suárez-Rico et al, 2021 ; Sun et al, 2020b ; Suzuki, 2022 ; Zanardo et al, 2020 ; Zeng et al, 2020 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…There were two multinational studies that recruited participants from five and 64 countries, respectively ( Basu et al, 2021 ; Ceulemans et al, 2021 ). The remaining 27 studies were conducted in 16 different countries over four continents ( Loret de Mola et al, 2021 ; Pariente et al, 2020 ; Racine et al, 2021 ; Silverman et al, 2020 ; An et al, 2021 ; Bo et al, 2020 ; Boekhorst et al, 2021 ; Ceulemans et al, 2020 ; Chrzan-Dętkoś et al, 2021 ; Fallon et al, 2021 ; Guvenc et al, 2021 ; Hamami et al, 2020 ; Hiiragi et al, 2021 ; Hui et al, 2021 ; Liang et al, 2020 ; Lorentz et al, 2020 ; Mariño-Narvaez et al, 2021 ; Molgora and Accordini, 2020 ; Oskovi-Kaplan et al, 2021 ; Ostacoli et al, 2020 ; Spinola et al, 2020 ; Stojanov et al, 2021 ; Suárez-Rico et al, 2021 ; Sun et al, 2020b ; Suzuki, 2022 ; Zanardo et al, 2020 ; Zeng et al, 2020 ). There were 16 cross-sectional studies that reported prevalence rates of psychological health symptoms during the COVID-19 pandemic ( An et al, 2021 ; Basu et al, 2021 ; Bo et al, 2020 ; Ceulemans et al, 2021 ; Ceulemans et al, 2020 ; Fallon et al, 2021 ; Guvenc et al, 2021 ; Liang et al, 2020 ; Molgora and Accordini, 2020 ; Oskovi-Kaplan et al, 2021 ; Ostacoli et al, 2020 ; Spinola et al, 2020 ; Stojanov et al, 2021 ; Suárez-Rico et al, 2021 ; Sun et al, 2020b ; Zeng et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation